(untitled) (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2019)
ABSTRACT Painted terrapin (Batagur borneoensis) is one of the reptiles found in the coastal area of Pusong Seruway Island, Aceh Tamiang Regency. Currently, the existence of wild population of painted terrapin is threatened to extinction due to factors of nature and community activities. The local government of Aceh Tamiang Regency has already protected painted terrapin (Batagur borneoensis) and listed it as protected species. This research is a descriptive exploratory survey to reveal the symptom and phenomenon of communities concerning their participation in the conservation of painted terrapin (Batagur borneoensis). Result of research was based on survey conducted in three villages with samples of 100 respondents given questionnaire through purposive random sampling technique. Data of ethnic communities consisted of; Tamiang, Aceh, Javanese, Batak and Arabic. Ethnozoology of communities obtained value local knowledge of communities as a form of awareness on animal protection included; participation in the sea turtle hatchling release, reduction in the exploitation activity of utilizing painted terrapin eggs (Batagur borneoensis) as srikaya (food) and traditional medicine, willingness not to take or disturb the animal and if they find painted terrapin (Batagur borneoensis), they will return the animal to its habitat or give it to the conservation team. A small part of the community joined in the assistance rescue group for painted terrapin (Batagur borneoensis). Â Keywords: ethnozoology, conservation of painted terrapin (Batagur borneoensis).